The Impact of Unplanned Excision on the Outcomes of Patients With Soft Tissue Sarcoma of the Trunk and Extremity: A Propensity Score Matching Analysis - Liang, Yao; Guo, Tian-Hui; Xu, Bu-Shu; Hong, Dong-Chun; Qiu, Hai-Bo; Zhou, Zhi-Wei; Zhang, Xing (Frontiers in Oncology, 2021)
Background Unplanned excision (UPE) of soft tissue sarcoma (STS) is often chosen in the early phase by general physicians without any radiological evaluation. Purpose The present study aimed to evaluate the impact of UPE on the clinical outcomes of patients with STS of the trunk and extremity. Materials and Methods Patients with STS of the trunk and extremity who underwent R0 resection between 1998 and 2016 were included and divided into the UPE and planned excision (PE) groups. Propensity score matching (PSM) was used to control the selection bias. The endpoints were disease-specific survival (DSS), local recurrence-free survival (LRFS), and metastasis-free survival (MFS). Results In total, 458 patients (277 males, 181 females; median age: 43 years) were included: 329 (71.8%) in the PE group and 129 (28.2%) in the UPE group. The follow-up time ranged from 7.1 to 313.78 months, with a median of 112.18 months. UPE patients were more likely to have a smaller or superficial lesion and were more frequently administered adjuvant therapy. After PSM, compared with the PE group, the UPE group had a longer LRFS (P=0.015), but there was no difference between the two groups regarding DSS and MFS. Residual disease was observed in 77.5% of the re-resected specimens in the UPE group and was a risk factor for DSS (P = 0.046) and MFS (P = 0.029) but was not associated with local recurrence (LR) (P=0.475) or LRFS (P=0.334). Moreover, we found no difference in DSS, LRFS or MFS according to the interval from UPE to definitive resection. Conclusion STS treated with UPE had distinct characteristics. Patients who undergo UPE followed by an additional wide R0 resection have similar oncological survival compared to patients who undergo an initial PE, although the high incidence of residual tumor in the UPE group leads to an unfavorable clinical course.